A Population Balance Approach to the Modelling of the CIP Process (The Southern African Institute of Mining and Metallurgy, 1987)
A method, based on the macroscopic population balance equation allowing the dynamic simulation of a multistage adsorption plant given an arbitrary rate expression, is described. The partial differential equations resulting from this method are simplified using the method of characteristics. The simplified equations can then be solved using standard ODE integration techniques. The procedure is illustrated by means of data typical of a CIP application. Requirements for data structures which allow the incorporation of the carbon-in-pulp (CIP) model (and other unit models) into a general metallurgical simulator are described. Based on these considerations, it is concluded that more generality in the description of distributed quantities such as loading and particle size is provided by the use of mass density at fixed class boundaries, rather than discrete masses within fixed classes as has hitherto been used by ore-dressing simulators.